2013
DOI: 10.1186/1750-1326-8-14
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral characterization of the 6-hydroxidopamine model of Parkinson’s disease and pharmacological rescuing of non-motor deficits

Abstract: BackgroundParkinson’s disease (PD) is a chronic neurodegenerative condition that is characterized by motor symptoms as a result of dopaminergic degeneration, particularly in the mesostriatal pathway. However, in recent years, a greater number of clinical studies have focused on the emergence of non-motor symptoms in PD patients, as a consequence of damage on the mesolimbic and mesocortical dopaminergic networks, and on their significant impact on the quality of life of PD patients. Herein, we performed a thoro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
97
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(119 citation statements)
references
References 77 publications
(82 reference statements)
20
97
0
2
Order By: Relevance
“…Although depression is a common non-motor symptom in PD, previous studies into depressive-like behaviors in different rat models of PD were less consistent (Winter et al, 2007;Branchi et al, 2008;Tadaiesky et al, 2008;Eskow Jaunarajs et al, 2010Santiago et al, 2010Santiago et al, , 2014Zhang et al, 2011;Delaville et al, 2012;Sourani et al, 2012;Carvalho et al, 2013;Hui et al, 2014). The discrepancy could be related to the site of 6-OHDA injection, the extent of DA depletion, unilateral or bilateral lesions, used depression paradigms and time frame for the behavior tests.…”
Section: Depressive-like Behaviors Involve Increased Burst-firing Actmentioning
confidence: 77%
See 1 more Smart Citation
“…Although depression is a common non-motor symptom in PD, previous studies into depressive-like behaviors in different rat models of PD were less consistent (Winter et al, 2007;Branchi et al, 2008;Tadaiesky et al, 2008;Eskow Jaunarajs et al, 2010Santiago et al, 2010Santiago et al, , 2014Zhang et al, 2011;Delaville et al, 2012;Sourani et al, 2012;Carvalho et al, 2013;Hui et al, 2014). The discrepancy could be related to the site of 6-OHDA injection, the extent of DA depletion, unilateral or bilateral lesions, used depression paradigms and time frame for the behavior tests.…”
Section: Depressive-like Behaviors Involve Increased Burst-firing Actmentioning
confidence: 77%
“…Previous studies into depressive-like behaviors in 6-hydroxydopamine (6-OHDA)-lesioned rats have been limited and divergent. These studies reported increased or unchanged depressive-like behaviors in different 6-OHDA rat models of PD (Winter et al, 2007;Branchi et al, 2008;Tadaiesky et al, 2008;Eskow Jaunarajs et al, 2010Santiago et al, 2010Santiago et al, , 2014Zhang et al, 2011;Delaville et al, 2012;Sourani et al, 2012;Carvalho et al, 2013;Hui et al, 2014). Further, a dysfunctional 5-HT system is generally regarded as a risk factor for depression, and accumulating lines of evidences also suggest that degeneration of the nigrostriatal pathway leads to an impairment of 5-HT system, with evidence including the loss of 5-HT neurons, reduction of brain 5-HT content, hyperactivity of 5-HT neurons and alterations in various types of 5-HT receptors (Scholtissen et al, 2006;Wang et al, 2009;Huot et al, 2011).…”
Section: Introductionmentioning
confidence: 94%
“…Catalepsy which is commonly assessed by bar test is a valid marker of the nigrostriatal neurodegeneration. 11,20 In rodents, this is a standard test for evaluation of 6-OHDA and neuroleptic drugsinduced akinesia. [21][22][23][24] In the present study we observed that intra-SNc injection of 6-OHDA resulted in motor impairments (increased catalepsy and decreased motorbalance) in rats which were attenuated by short term treatment with SM.…”
Section: Discussionmentioning
confidence: 99%
“…In rotarod, which is considered as a standard test for evaluation of motor-balance, performance is measured by the period of time that an animal stays up and walks on the rod and the latency to fall off the drum was recorded. 20,25,36 In 6-OHDA-lesioned rats loss of dopaminergic neurons and reduction of striatal dopamine levels is an essential cause of motor incoordination. In fact, unilateral lesion of SNc obliges animal to change its weight irregularly for movement and balance; therefore this lead to motor disturbance and asymmetry.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26][27] A good correlation between the drug-induced rotations and the severity of the disease was established in intra-nigral 6-hydroxydopamine (6-OHDA)-infused rats. 28 We investigated correlation, if any, between dopaminergic cell loss in the substantia nigra pars compacta (SNpc) and unilateral bias in turning to find if the rotational severity, nigral dopaminergic cell loss, and striatal DA content, singularly or together, could be set as a scale for the severity of or stage the disease in rats unilaterally lesioned with 6-OHDA or 1-methyl-4-phenyl pyrinidium (MPP + ). A change from negative to positive correlation of nigral neuronal loss or striatal denervation with that of the performance in behavioral tests provides a scale for the assessment of functional recovery in cell transplantation studies.…”
Section: Introductionmentioning
confidence: 99%